2006
DOI: 10.1007/s10529-006-9163-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic manipulation of a primary metabolic pathway for l-ornithine production in Escherichia coli

Abstract: Metabolic engineering has been used to improve L-ornithine biosynthesis in Escherichia coli W3110. L-Ornithine production increased from 0.3 to 3.2 mg/g (dry cell weight) when the primary L-ornithine biosynthetic pathway was optimized by disrupting the pathway transcription repressor, thereby increasing the expression of the genes involved in the pathway, and by preventing conversion of L-ornithine into citrulline. When a feedback-resistant N-acetylglutamate synthetase gene (argA214) was placed under the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…It may also be used to enhance the flux to L-ornithine. Only three papers reported the results of enhance of L-ornithine production by metabolic engineering so far [10][11][12]. Lee and Cho [10] reported that an engineered E. coli W3110 ( argFargIargRproBspeFP araB -arg214) produced L-ornithine of 13.2 mg/gDCW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be used to enhance the flux to L-ornithine. Only three papers reported the results of enhance of L-ornithine production by metabolic engineering so far [10][11][12]. Lee and Cho [10] reported that an engineered E. coli W3110 ( argFargIargRproBspeFP araB -arg214) produced L-ornithine of 13.2 mg/gDCW.…”
Section: Introductionmentioning
confidence: 99%
“…Only three papers reported the results of enhance of L-ornithine production by metabolic engineering so far [10][11][12]. Lee and Cho [10] reported that an engineered E. coli W3110 ( argFargIargRproBspeFP araB -arg214) produced L-ornithine of 13.2 mg/gDCW. Hwang et al [11] also reported that cooverexpression in a triple gene knockout Corynebacterium glutamicum (argFargR proB) resulted in L-ornithine production of 16.49 mg/g DCW, L-ornithine concentration of 179.14 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 lists the bacterial strains and plasmids used in this study. Wild-type strain C. glutamicum ATCC 13032 (American Type Culture Collection, Manassas, VA) and mutant strain C. glutamicum SJC 8074 (provided by Sangji University, South Korea) (10) were grown at 30°C in Luria-Bertani medium (29) and, for the production of ornithine and arginine, in mineral medium containing yeast extract (MMY) ) (17). In a 250-ml shake flask, a 1-ml preculture was inoculated into 50 ml of MMY medium.…”
Section: Methodsmentioning
confidence: 99%
“…Many papers have reported that L-ornithine can be produced from glucose by a citrulline-or arginine-requiring mutant of Brevibacterium ketoglutamicum (Choi et al 1996;Lee et al 2000), Corynebacterium glutamicum (Zhang et al 2009), or engineered C. glutamicum (Lee and Cho 2006;Hwang et al 2008;Hwang and Cho 2010, 2014Lee et al 2010b;Lu et al 2011Lu et al , 2012Jiang et al 2013a, b). However, glucose is commonly obtained from starch hydrolysis by a high-temperature saccharification process combined with α-amylase and glucoamylase (Khaw et al 2007).…”
Section: Introductionmentioning
confidence: 99%